Smart Egg Incubator Monitoring System Based on IoT and Blynk Connectivity - Santosa, Slamet Purwo; Jaylana, Jaky; Naibaho, Nurhabibah (Jurnal Teknik Elektro Indonesia, 2025)
In the era of Industry 4.0, the integration of Internet of Things (IoT) technologies in agriculture has significantly enhanced automation and remote monitoring capabilities. This research presents the development of a smart egg incubator monitoring system based on the ESP32 microcontroller, integrated with various sensors and connected through the Blynk IoT platform. The system incorporates a DHT22 sensor for real-time temperature and humidity monitoring, a MAX9814 microphone amplifier for detecting chick hatching sounds, and an ESP32-CAM module for live video streaming inside the incubator. All collected data and alerts are transmitted to the user via the Blynk application, enabling remote supervision and timely interventions. The incubator is designed to maintain optimal environmental conditions, with automatic control of heating and cooling systems based on sensor feedback. Experimental results show that the system successfully maintained a stable incubation environment with an average temperature of 37.3°C and humidity around 55%, and accurately detected hatching events through sound analysis. The implementation of live video streaming further enhances the monitoring capabilities by allowing visual confirmation of embryo development. The proposed system demonstrates a reliable, scalable, and user-friendly solution for modern poultry farming, especially in resource-limited or remote environments